2001
DOI: 10.1530/rep.0.1220205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrition and environmental factors on the fetal programming of the reproductive axis

Abstract: Research from a wide range of scientific disciplines has shown that the reproductive performance of animals in adult life is determined, in part, by a variety of extraneous influences acting at different stages of development from before conception until after birth. These effects are probably mediated through changes in the hypothalamic-pituitary and gonadal axes but the physiological system that is affected depends on the stage of development at which the influence is applied. The physiological mechanisms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(49 citation statements)
references
References 24 publications
1
44
0
4
Order By: Relevance
“…Nutrition is the major intrauterine environmental factor that alters expression of the fetal genome and may have lifelong consequences (fetal programming). Alterations in fetal nutrition and endocrine status may result in developmental adaptations that permanently change the structure, physiology and metabolism of the offspring, predisposing individuals to metabolic, endocrinological and cardiovascular diseases in adult life [24,29]. Animal studies have shown that both maternal under-and overnutrition reduce placental-fetal blood flow and stunt fetal growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrition is the major intrauterine environmental factor that alters expression of the fetal genome and may have lifelong consequences (fetal programming). Alterations in fetal nutrition and endocrine status may result in developmental adaptations that permanently change the structure, physiology and metabolism of the offspring, predisposing individuals to metabolic, endocrinological and cardiovascular diseases in adult life [24,29]. Animal studies have shown that both maternal under-and overnutrition reduce placental-fetal blood flow and stunt fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…According to Rhind et al [24], it is clear that environmental factors can greatly alter the development of the fetal hypothalamic-pituitary axis and gonadal structure and physiology, including number of cells, enzyme systems and hormonal output, which is particularly marked during the period of rapid gonadal development and differentiation as demonstrated by Bielli et al [1] in reduced numbers of Sertoli cells in the newborn lamb due to low maternal nutrition. Therefore, in addition to possible genetic factors which are thought to be involved in gonadal growth and differentiation [2,3,11,16,18,25], the environmental and predominantly nutritional factors should be also considered as a cause of MPH.…”
Section: Discussionmentioning
confidence: 99%
“…1), hence rendering interspecies comparison somewhat difficult. For example, although meiosis begins during pregnancy in humans, sheep, and mice, gonial mitotic division is only completed in humans and sheep during this period, whereas it continues after birth in mice [9,10]. Subsequently, folliculogenesis and the accompanying steroidogenesis take place during fetal life in humans and sheep, but only shortly after birth in mice.…”
Section: Gonadal Developmentmentioning
confidence: 99%
“…Maternal BMI before conception and maternal weight gain during pregnancy may be indicators of the maternal nutritional status and are also used as indicators of fetal nutrition [9]. In terms of reproduction, premature onset of puberty was observed in girls born from mothers with high BMI (Ͼ25 kg.m Ϫ2 ) [41].…”
Section: Maternal Weight Before Pregnancymentioning
confidence: 99%
“…During this 'window of opportunity', each organ is susceptible to being targeted for reprogramming by a stimulus or stressor such as maternal nutrient restriction or supplementation or stress such as excessive heat or maternal psychological stress (Brameld and Daniel, 2008). A nutritional or hormonal imbalance during this developmental period could cause permanent impairment of the affected organ with negative consequences for the long term health of the individual (Rhind et al, 2001). Fetal programming research was initially based on human epidemiological studies (Barker, 1992a(Barker, ,b, 1995 and this was expanded upon in controlled experiments using laboratory animals (Lesage et al, 2004;Langley-Evans et al, 1996).…”
Section: Introductionmentioning
confidence: 99%